OBTAINING LIQUID FERTILIZERS WITH PHYSIOLOGICALLY ACTIVE SUBSTANCES - Saidullaeva G. A; Tadjiyeva X. S,; Abdullaeva M.T. (Web of Journals Publishing, 2024)
The paper substantiates the process of obtaining liquid fertilizers based on solutions of potassium sulfate, ammonium nitrate, urea, copper sulfates, and monoethanolammonium. The dependence of changes in the physicochemical properties of solutions on the composition of the components is studied. Based on the data obtained, diagrams of "composition-properties" are constructed.
Keywords: solution, urea, diagram, system, ammonium nitrate, potassium sulfate, fertilizers, properties, composition, ratios.